DA'WAH RELIGIOUS MODERATION IN INDONESIA: Comparison of HMI Lafran Pane and PMII Mahbub Djunaidi Thought Studies - Marissakh Diana Martabillah (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2024)
ABSTRACT This study aims to analyze the similarities and differences in the thoughts of HMI Lafran Pane (LP) and PMII Mahbub Djunaidi (MD) regarding religious moderation da'wah. This research is library research and comparative qualitative research by analyzing two figures. Primary sources are all LP and MD works, and other works related to the theme as secondary sources. The results of this study stated that; 1) the thoughts of Lafran Pane as the initiator of HMI and Mahbub Djunaidi as the founder of PMII represent religious moderation behavior, especially in national commitment, 2) both figures have a positive influence on the next generation in each organization. Like Nurcholish Madjid, HMI, and KH cadres. Ahmad Bagja, a cadre of PMII, 3) PMII presented the da'wah of moderation in the sphere of nationalism while HMI had an attitude and nature of moderation. Both organizations have similar ideologies regarding the meaning of moderation both in the sphere of religion as well as nationality and state. The importance of moderation is because Indonesia is a plural country with a variety of races and tribes, if this plurality is not maintained and considered as a positive thing we should be grateful for the impact that will harm all people. If you do not have a moderate nature, there will be divisions due to different ideas, behaviors, and beliefs. So the goal is to know and understand how students do not tend to be conservative in groups according to individual beliefs. Keywords: Student Organization, Lafran Pane, Mahbub Djunaidi, Religious Moderation, Da'wah. ABSTRAK Penelitian ini bertujuan menganalisis persamaan dan perbedaan pemikiran HMI Lafran Pane (LP) dan PMII Mahbub Djunaidi (MD) tentang dakwah moderasi beragama. Penelitian ini merupakan penelitian kepustakaan (library research) dan penelitian kualitatif komparatif dengan menganalisis dua tokoh. Sumber primer adalah semua karya LP dan MD, dan karya lain yang berkaitan dengan tema sebagai sumber sekunder. Hasil penelitian ini menyatakan bahwa; 1) pemikiran Lafran Pane sebagai penggagas HMI dan Mahbub Djunaidi selaku pendiri PMII merepresentasikan perilaku moderasi beragama khususnya dalam komitmen kebangsaan, 2) kedua tokoh sama-sama memberikan pengaruh positif bagi generasi berikutnya di masing-masing organisasi. Seperti Nurcholish Madjid kader HMI dan KH. Ahmad Bagja kader PMII, 3) PMII mempresentasikan dakwah moderasi di lingkup nasionalisme sedangkan HMI mempnyai sikap dan sifat moderasi. Kedua organisasi memiliki ideologi serupa terkait makna moderasi baik dalam lingkup agama juga kebangsaan dan bernegara. Pentingnya moderasi sebab Indonesia merupakan negara yang plural dengan beraneka ragam ras dan suku, kemajemukan tersebut jika tidak dipelihara dan dinilai sebagai hal positif yang patut disyukuri dampaknya akan merugikan seluruh oknum. Jika tidak memiliki sifat moderat akan terjadi perpecahan akibat berbedanya gagasan, tingkah laku, dan keyakinan. Maka tujuannya untuk mengetahui dan memahami bagaimana mahasiswa tidak cenderung konservatif berkelompok-kelompok sesuai keyakinan individu. Keywords: Organisasi Mahasiswa, Lafran Pane, Mahbub Djunaidi, Moderasi Beragama, Dakwah.